2015
DOI: 10.1073/pnas.1514598112
|View full text |Cite
|
Sign up to set email alerts
|

A vacuolar phosphate transporter essential for phosphate homeostasis inArabidopsis

Abstract: Inorganic phosphate (Pi) is stored in the vacuole, allowing plants to adapt to variable Pi availability in the soil. The transporters that mediate Pi sequestration into vacuole remain unknown, however. Here we report the functional characterization of Vacuolar Phosphate Transporter 1 (VPT1), an SPX domain protein that transports Pi into the vacuole in Arabidopsis. The vpt1 mutant plants were stunted and consistently retained less Pi than wild type plants, especially when grown in medium containing high levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
162
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(183 citation statements)
references
References 41 publications
11
162
2
Order By: Relevance
“…When ectopically expressed in the vacuoles of Nicotiana benthamiana mesophyll cells, VPT1 could mediate several anions influx across the tonoplast, including Pi, SO 4 2¡ , NO 3 ¡ , Cl ¡ , and malate with Pi as that preferred anion. 3 Complementary to our results, 31 P-magnetic resonance spectroscopy analysis revealed that loss-of-function of vpt1 mutants accumulated less Pi and exhibited a lower vacuolar-to-cytoplasmic Pi ratio than the wild types. 4 Taken together, these results indicate that the members of SPX-MFS family are the candidate transporters conducting Pi across the tonoplast.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…When ectopically expressed in the vacuoles of Nicotiana benthamiana mesophyll cells, VPT1 could mediate several anions influx across the tonoplast, including Pi, SO 4 2¡ , NO 3 ¡ , Cl ¡ , and malate with Pi as that preferred anion. 3 Complementary to our results, 31 P-magnetic resonance spectroscopy analysis revealed that loss-of-function of vpt1 mutants accumulated less Pi and exhibited a lower vacuolar-to-cytoplasmic Pi ratio than the wild types. 4 Taken together, these results indicate that the members of SPX-MFS family are the candidate transporters conducting Pi across the tonoplast.…”
supporting
confidence: 83%
“…6 We found that the transgenic plants expressing At1g63010 with a green fluorescent protein (GFP) fusion displayed the fluorescent signals specifically detected in the tonoplast, and thus named this gene as VPT1 (Vacuolar Phosphate Transporter 1). 3 The subcellular location of VPT1 in the tonoplast was further confirmed in an independent study, where it was named as PHT5;1 (PHOSPHATE TRANSPORTER 5;1).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…This inability of tDT to accept sulphate and phosphate as substrates concurs, however, with the presence of specific PO 4 2--and SO 4 2-carriers in the vacuolar membrane (33,34). It appears likely that the functions of the latter carriers in controlling cellular phosphate-and sulphate homeostasis would be hampered by the simultaneous presence of additional carboxylate/SO 4 2--or carboxylate/PO 4 2--transport capacity across the tonoplast.…”
Section: -) Formmentioning
confidence: 68%
“…In contrast, PHT2 proteins are localized in chloroplasts, while PHT3/MPT proteins are mostly mitochondrial membrane transporters and PHT4 proteins are Golgi-apparatus located transporters. A vacuolar Pi transporter was identified in Arabidopsis and designated as PHT5/VPT/SPX-MFS proteins [26].…”
Section: Phosphate Uptake and Transport In Wheat And Arabidopsismentioning
confidence: 99%